IDENTIFIKASI GALUR-GALUR PADI MUTANINSERSI TOLERAN DAN RENTAN CEKAMAN SALINITAS BERDASARKAN KARAKTER MULTIVARIAT PERTUMBUHAN DAN BIOKIMIA PADA FASE VEGETATIF - Situmorang, Apriadi; Zannati, Anky; Widyajayantie, Dwi; Nugroho, Satya (BERITA BIOLOGI, 2011)
Growth and biochemical characters of thirty-three Nipponbare-based rice mutant lines independently harboring activation-tag in salt stress condition were investigated. Rice cv Nipponbare wild type, IR29 and Pokkali were used as isogenic, susceptible, and tolerant cultivars, respectively. Plants were grown in Yoshida nutrient solution containing NaCI (6 g/1) as the stress treatment and in Yoshida nutrient solution without NaCI as the control. Evaluation of salt tolerance was conducted at 21 days after salinization.The results showed that there was a significant difference in growth characters among genotypes in reduction of the plant height,root length, shoot fresh weight, root fresh weight, shoot dry weight, as well as in the root dry weight. Biochemical characters of the genotypes also showed significant difference in their reduction of chlorophyll-a and chlorophyll-b concentrations,total carotenoids and proline accumulation. Based on multivariate growth and biochemical characters,T3.PMO.VI.63.5a.30.9,T3.PMO.VI.30.1a.21.1, T3.PMO.V1.63.5a.33.7F3.PUR.IX.49.1d.l.6.5,T3.PMO.VI.81.3a.4.4, F3.PUR.IX.49.1d.l.6.5,and F3.PUR.VIII.5.1f.l.4.8 were assumed as potential salt-tolerant lines, respectively, while mutant lines T3.PMO.VI.30.1a.l07.7,T3.PMO.VI.63.5a.20.6,T3.PMO.III.4.4c.7.2,andT3.PMO.VI.30.1a.51.1 were assumed as salt-susceptible lines respectively.